The Impact of SRSD-Based ChatGPT Use on EFL Students’ Writing Anxiet - Elsa, Elsa; Wu, Ting-Ting (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study explores the effect of structured versus unstructured use of ChatGPT on writing anxiety among learners of English as a foreign language (EFL). Although AI tools like ChatGPT are becoming more prevalent in language classrooms, their ability to reduce learners’ anxiety remains unclear, particularly when implemented without instructional support. To address this gap, the study employed a quasi-experimental design involving 62 students from two intact EFL classes. One group used ChatGPT with guidance based on the Self-Regulated Strategy Development (SRSD) model, while the other used it without structured support. Writing anxiety was measured before and after the intervention, and analysis of covariance (ANCOVA) was used to compare post-test scores while controlling for pre-test levels. The results revealed a statistically significant difference between the two groups (p < .01, partial η2 = .144), indicating that the SRSD-based use of ChatGPT more effectively reduced students’ writing anxiety. These findings highlight the importance of embedding pedagogical frameworks into AI-assisted language learning to support students’ emotional and cognitive needs.